Karakteristik Pergerakan Kendaraan Bermotor Di Dki Jakarta - Maimunah, Siti (Warta Penelitian Perhubungan, 2010)
vehicles. DK! Jakarta as a center of business and government result in the movement of vehiclesduring the dmj can reach twia! at night. The purpose of the study is to characterize the movement ofmotorized vehicles iri Jakarta, so it can re used as input in the transportation planning in Jakarta in thefuture. A suruetj was condUcted at 9 gas stations in_ Cililitan, Daan Mogot, · Karang Tengah, KelapaGading, Bekasi, Margonda, East Jakarta, Pramuka and Warung Jambu Bogar. Based on surveydata, the analysis .shaws that 694 or about 42% is a movement in Jakarta. Number of vehicles mostminibuses are the h;pes of vehicles which mm;e in. the Jakarta area that is equal. to 57.35% and theaverage number of f"lSsengers per vehicle is 2.16 people per vehicle mileage is 28.2 KM. The intent ofthe majority of respondents travel to work is 74.06%. This situation illustrates that the mobility ofpeople and vehicles in Jakarta is ven; high with the distance far enough (from outside DKI Jakarta).To anticipate this condition, it is rerommended for mass transportation development not only in thecities of Jakarta, but also connects surrounding towns like Bogar, Depok, Tangerang and Bekasi.